PENERAPAN CLOUD COMPUTING PADA SISTEM KASIR DIGITAL DI TOKO SEMBAKO MAK & ABAH - M. Rangga Juliyakta; Ferliansyah; Bayu Fajar Susanto (Fakultas Ekonomi dan Bisnis, 2025)
This study discusses the application of cloud computing technology to the digital cashier system at Mak & Abah Grocery Store as a solution to improve efficiency and accuracy in managing sales transactions. Along with the growing need for digitalization in the micro and small business sector, the use of a cloud-based cashier system is a modern alternative that can replace conventional methods that are prone to recording errors and data loss. In this study, the cashier system was developed using a cloud-based platform that allows real-time transaction recording, centralized data storage, and flexible access from various devices. The research method involved direct observation, interviews with shop owners, and system trials for a certain period. The implementation results showed an increase in store operational efficiency by 35%, a reduction in transaction recording errors, and ease in preparing daily sales reports. Thus, the application of cloud computing has been proven to have a positive impact on the digitalization of grocery store operations and has the potential to be applied more widely in the MSME sector.